2005
DOI: 10.1107/s1600536805018465
|View full text |Cite
|
Sign up to set email alerts
|

5-Butyl-6-methyl-2-thioxo-2,3-dihydropyrimidin-4(1H)-one

Abstract: In the title compound, C9H14N2OS, the but­yl group is disordered over two orientations. In the crystal structure, the inversion‐related mol­ecules are linked by N—H⋯O [N⋯O = 2.823 (3) Å] and N—H⋯S [N⋯S = 3.346 (2) Å] hydrogen bonds to form chains along [210].

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2011
2011
2014
2014

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 3 publications
0
3
0
Order By: Relevance
“…The C S bond is similar to the corresponding bond in the parent 2-thiouracil [1.683 (3) Å ; Tiekink, 1989]. In the crystal packing of (1), there are N-HÁ Á ÁO and N-HÁ Á ÁS hydrogen bonds (Hu et al, 2005;Long et al, 2005) (Table 2). Compound (2), an S-alkylated derivative of (1), crystallizes in the space group C2/c with one molecule in the asymmetric unit ( Fig.…”
Section: Resultsmentioning
confidence: 77%
“…The C S bond is similar to the corresponding bond in the parent 2-thiouracil [1.683 (3) Å ; Tiekink, 1989]. In the crystal packing of (1), there are N-HÁ Á ÁO and N-HÁ Á ÁS hydrogen bonds (Hu et al, 2005;Long et al, 2005) (Table 2). Compound (2), an S-alkylated derivative of (1), crystallizes in the space group C2/c with one molecule in the asymmetric unit ( Fig.…”
Section: Resultsmentioning
confidence: 77%
“…Nine of these structures show R 2 2 (8) motifs with two N-HÁ Á ÁO hydrogen bonds [refcodes FAJWES (Brewer et al, 1987), FICBEY , HEPMIY (Pastor et al, 1994), MUYTIK (Ivanova & Spiteller, 2010), HAFLAC (Antoniadis et al, 2003), LACJIJ (Tashkhodzhaev et al, 2002), EBAQOP (Balas et al, 2011), and EBAQOP01 and DAYGUH (Kubicki et al, 2012)] and 11 structures contain R 2 2 (8) motifs characterized by two N-HÁ Á ÁS hydrogen bonds [FALWOF (Orzeszko et al, 2004), FUWBOP (Medda et al, 2009), LOFDAL (Fonar et al, 1999), MUGMIK (Matković-Č alogović et al, 2002), PABNAJ, PABNIR (Chierotti et al, 2010), QAYCID (Van Hecke et al, 2005), QEHSEB (Tiekink, 2001), ZZZGEO01 (Delage, H'Naifi, Goursolle & Carpy, 1986), and CALFUS and CALGAZ (Tutughamiarso & Egert, 2011)]. In nine structures, two different R 2 2 (8) motifs with either two N-HÁ Á ÁO or two N-HÁ Á ÁS hydrogen bonds can be observed [CASPUI (Hu et al, 2005), GEMCAC (Read et al, 1988), PABPAL (Chierotti et al, 2010), RAPNAY (Long et al, 2005), TURCIL01 (Tiekink, 1989), TURCIL02 (Munshi & Guru Row, 2006), UXIXUV (Ferreira et al, 2011), UXIXUV01 (Tutughamiarso & Egert, 2011) and LANZIL (Al-Deeb et al, 2012)].…”
Section: Figurementioning
confidence: 99%
“…19 entries showed R 2 2 (8) motifs characterized by two N-HÁ Á ÁO hydrogen bonds; the S atoms take part as acceptors only in five of them [refcodes LACJIJ (Tashkhodzhaev et al, 2002), XUHJIY (Pawlowski et al, 2009), XEXWAZ, XEXWED and XEXWIH (Balalaie et al, 2006)], whereby chains stabilized by N-HÁ Á ÁS hydrogen bonds are observed only in XUHJIY. Nine structures contain two different R 2 2 (8) patterns with either two N-HÁ Á ÁO or two N-HÁ Á ÁS hydrogen bonds [refcodes CASPUI (Hu et al, 2005), CUKBOA (Hori et al, 2009), GEMCAC (Read et al, 1988), PABPAL (Chierotti et al, 2010), RAPNAY (Long et al, 2005), TURCIL01 (Tiekink, 1989), TURCIL02 (Munshi & Guru Row, 2006), WIVJAM (Coxall et al, 2000) and ZEWDOU (Ferrari et al, 1995)]. Furthermore, six entries showed R 2 2 (8) interactions consisting of two N-HÁ Á ÁS hydrogen bonds [refcodes FALWOF (Orzeszko et al, 2004), JESWEK (Xue et al, 2006), MTURAC (Hawkinson, 1975), PABNIR (Chierotti et al, 2010), VOKBUT (Luo et al, 2008) and ZUWMUZ (Branch et al, 1996)].…”
Section: Figurementioning
confidence: 99%